Prevention of Road Accidents by Using Smart Device - Ragaleela Dalapati Rao*, K.Satya Eswara Rao, B.Pooja, J.Venkateswara Naik (International Journal of Control and Automation, 2020)
In these present days accidents has been increasing day by day. In this situation it is necessary to save the life against accidents. In order to stop an accident before it happens, lessen the degrees of injury, save lives and to escape from injuries we are developing a smart device which protects from accidents. This project is to develop a protective device which is capable to prevent accidents by incorporating Eye blink detector, ultra-sonic sensor, fire detector and alcohol detector, GSM module. The main component here is the ARDUINO that supervises the entire process.